1981
DOI: 10.1021/jm00144a024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro antimicrobial property of o-carborane derivatives

Abstract: Various o-carboranes and nido-type dicarbollide anions have been synthesized and tested for antimicrobial activity. Nearly all of the dicarbollide monoanions investigated were active in vitro against fungi such as Candida albicans, Aspergillus fumigatus, and Tricophyton asteroides, as well as against Gram-positive bacteria. From a consideration of the structure-activity relationships, it seems most reasonable to conclude that the introduction of lipophilic alkyl or o-carboranyl groups to the hydrophilic dicarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…To the best of our knowledge, there is no other publication available that deals with such a topic. However, it should be noted that it has already been reported that COSAN.Na and some of the related compounds have a very high antibacterial activity against the planktonic growth of Gram-positive cocci [ 30 , 31 , 32 , 36 , 44 ]; thus, it can be used as an inhibitory agent alone. Despite this, there may be cases where a combination of antibiotics with COSAN.Na will be desirable due to their different mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there is no other publication available that deals with such a topic. However, it should be noted that it has already been reported that COSAN.Na and some of the related compounds have a very high antibacterial activity against the planktonic growth of Gram-positive cocci [ 30 , 31 , 32 , 36 , 44 ]; thus, it can be used as an inhibitory agent alone. Despite this, there may be cases where a combination of antibiotics with COSAN.Na will be desirable due to their different mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies brought positive information about the antimicrobial activity of various bis- o -dicarbaboranes, closo - o -dicarbaboranes, and nido -type dicarbollide anions towards the representatives of microscopic fungi and bacteria Staphylococcus aureus , Streptococcus pyogenes , Escherichia coli , Klebsiella pneumoniae , Mycobacterium spp., Enterobacter cloacae , Pseudomonas aeruginosa , Acinetobacter baumannii , etc. [ 36 , 37 , 38 , 39 , 40 , 41 ]. More information about these properties was published in an article focused on the antimicrobial activity of COSAN derivatives [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…( 18) Minagawa, H.; Kitaura, K.; Mineura, K.; Marumo, H. Shinkin to Shinkinsho 1983, 24, 234. to in vitro and in vivo activity. Replacement of the halogen by hydrogen, methyl, and methoxy groups produces negative effects (1,4,5,10,14,15,20,21,26). Replacement of the phenyl group in R2 of I by an alkyl group (43-53) causes loss of in vitro and in vivo activity, with the retaining of some activity in Rv The size of the alkyl group in Rx plays an important role in the high activity in vivo.…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
“…So far, no research has to our knowledge concerned antimicrobial photodynamic effect of boronated carboranes, although photodynamic inactivation (PDI) of bacteria has long been studied with different photosensitizers [ 16 32 ] resulting in a great variety of medicinal applications. Of note, some data on dark bactericidal and fungicidal activity of 1-(aminoalky)-1,2-dicarba- closo -dodecaborane [ 33 ] and o -carboranylalanine [ 34 ] were earlier reported. The cytotoxic efficacy of derivatives of polyhedric boron complexes could be related to their unique binding [ 35 ] and membrane-penetrating [ 36 , 37 ] properties, the latter being associated with delocalization of their charge.…”
Section: Introductionmentioning
confidence: 99%